Study on Combined Quantitative Light-Induced Fluorescence (QLFTM) and Calcium Assay for Screening of Remineralization Potential of Human Saliva - Daisuke Inaba; Kyoko Kohda; Elbert de Josselin de Jong (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
The present study determined biological distributions of salivary ion levels of calcium and phosphate among adult populations and secondly examined the impact of salivary calcium contents to enamel remineralization as measured by combined Quantitative Light-induced Fluorescence (QLFTM) and a human saliva model (HSM) as an ex vivo experimental system employing whole saliva as a reaction mixture for mineral resources. Salivary mineral contents were focused in this study and it was found that levels of salivary calcium and phosphate ions ranged extensively among individuals. From clinical view point, the present results suggested that (1) there could be some populations whose remineralization potential is insufficient resulting in at higher risk in dental caries, and (2) QLFTM was sensitive enough to detect saliva-induced mineral recovery of enamel within 24 hours and the combined means of HSM and QLFTM could be as a non-invasive clinical test to screen remineralization (caries recovery) potential of human saliva samples.